The cult of saints in Nidaros archbishopric manuscripts, miracles, objects - Bø, Ragnhild M. 1975-; Jón Viðar Sigurðsson 1958- (Brepols, 2022)
Scandinavia has often been considered as a peripheral part of the Christian world, with its archbishopric in Nidaros an isolated outpost of the Catholic Church. This volume, however, offers a reassessment of such preconceptions by exploring the way in which the Nidaros see celebrated the cult of saints and followed traditions that were both part of, and distinct from, elsewhere in Christian Europe. The contributions gathered here come from specialists across different disciplines, among them historians, philologists, art historians, and epigraphists, to offer a multifaceted insight into how texts and objects, sculpture, runes, and relics all drove the cult of saints in this northern corner of Europe. In doing so, the volume offers a nuanced understanding of the development of cults, the saints themselves, and their miracles, not only in the Norse world, but also more widely.
Keywords: Geschichte 1000-1537; Christianisierung; Heiligenverehrung; Norwegen; Island; Diözese Trondheim; Orkneyinseln; Aufsatzsammlung